2017
DOI: 10.3389/fcimb.2017.00406
|View full text |Cite
|
Sign up to set email alerts
|

Immunofibrogenic Gene Expression Patterns in Tanzanian Children with Ocular Chlamydia trachomatis Infection, Active Trachoma and Scarring: Baseline Results of a 4-Year Longitudinal Study

Abstract: Trachoma, caused by Chlamydia trachomatis, is the world's leading infectious cause of blindness and remains a significant public health problem. Much of trachomatous disease pathology is thought to be caused indirectly by host cellular and immune responses, however the immune response during active trachoma and how this initiates progressive scarring is not clearly understood. Defining protective vs. pathogenic immune response to C. trachomatis is important for vaccine design and evaluation. This study reports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(58 citation statements)
references
References 94 publications
6
52
0
Order By: Relevance
“…In February 2012, we recruited a cohort of children from three adjacent trachoma endemic villages in Kilimanjaro and Arusha regions, Northern Tanzania. All children, between the ages 3 and 11 years, who were normally resident in one of the three villages, were eligible for inclusion (n =666) [7]. 616 children were enrolled and the cohort was initially followed-up every 3 months for 4 years, for a total of 17 time points.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In February 2012, we recruited a cohort of children from three adjacent trachoma endemic villages in Kilimanjaro and Arusha regions, Northern Tanzania. All children, between the ages 3 and 11 years, who were normally resident in one of the three villages, were eligible for inclusion (n =666) [7]. 616 children were enrolled and the cohort was initially followed-up every 3 months for 4 years, for a total of 17 time points.…”
Section: Methodsmentioning
confidence: 99%
“…Timepoint 14 (August 2015) was selected for this evaluation and 428 children were seen, 9 months after the last mass community treatment with antibiotic as detailed by the SAFE strategy. Conjunctival swabs were collected as previously described using sterile polyester-tipped swabs [7,8]. The rst swab was collected into 250µl RNA later and was used elsewhere [7][8][9], whilst the second swab was collected dry and stored at -80°C until used in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In aberrant wound healing, LCs stimulated naive T cell responses, and identify the triggering receptor expressed on myeloid (TREM)‐1, a member of the Ig immunoregulatory receptor family, infiltrating hypoxic areas of active HSs, pointing to the pathogenic role in wound repair disorders . Besides, it has been found that there is a correlation of NK cell, T‐cell, and scarring . For example, NK cells inhibit the progression of liver fibrosis through targeting and clearing the hepatic astrocytes directly which secrete ECM, suggesting an important role in antifibrosis .…”
Section: Conclusion and Prospectmentioning
confidence: 99%
“…186 Besides, it has been found that there is a correlation of NK cell, T-cell, and scarring. 187 For example, NK cells inhibit the progression of liver fibrosis through targeting and clearing the hepatic astrocytes directly which secrete ECM, suggesting an important role in antifibrosis. 188 Also, we mentioned in the previous section that macrophages of different phenotypes play different roles in the scar formation.…”
Section: Conclusion and Prospectmentioning
confidence: 99%